Pembangunan Website Paket Travel dan Sewa Mobil Berbasis Arsitektur Microservices - Made Riksi Purnama Sadnya Agung; Sidhi, Thomas Adi Purnomo; Ardanari, Patricia (Jurnal Informatika Atma Jogja, 2025)
The tourism sector in Bali continues to grow, but Bali Travel Ride still faces challenges in managing bookings and finances due to manual systems. To address this, a microservices-based website was developed to integrate travel package and car rental booking services, simplifying business operations. This research includes literature study, system architecture design, and system development using Next.js on the front-end and Nest.js on the back-end, with payment integration through a Payment Gateway. The deployment process utilizes Docker, Nginx as a load balancer, and Cloudflare Tunnel for public access. The results of Black Box testing show that all features function according to specifications. The implementation of the microservices architecture has proven to enhance flexibility and scalability, allowing each service to be developed independently without affecting others, while simplifying the management of bookings, payments, and financial reports.   Sektor pariwisata Bali terus berkembang, namun Bali Travel Ride masih terkendala dalam pengelolaan pemesanan dan keuangan karena sistem manual. Untuk mengatasinya, dikembangkan website berbasis microservices yang mengintegrasikan layanan pemesanan paket travel dan sewa mobil agar mempermudah operasional bisnis. Penelitian ini mencakup studi literatur, perancangan arsitektur, serta pengembangan sistem menggunakan Next.js di front-end dan Nest.js di back-end dengan pembayaran menggunakan Payment Gateway. Proses deployment dilakukan dengan Docker, Nginx sebagai load balancer, dan Cloudflare Tunnel untuk akses publik. Hasil pengujian Black Box menunjukkan seluruh fitur berfungsi sesuai spesifikasi. Penerapan arsitektur microservices terbukti meningkatkan fleksibilitas dan scalability, memungkinkan setiap layanan dikembangkan secara independen tanpa mengganggu sistem lain, sekaligus mempermudah pengelolaan pemesanan,